Enhancement of light emission in Bragg monolayer-thick quantum well structures - Pozina, Galia (Sci Rep, 2019)
Control over spontaneous emission rate is important for improving efficiency in different semiconductor applications including lasers, LEDs and photovoltaics. Usually, an emitter should be placed inside the cavity to increase the spontaneous emission rate, although it is technologically challenging. Here we experimentally demonstrate a phenomenon of super-radiance observed in a cavity-less periodic Bragg structure based on InAs monolayer-thick multiple quantum wells (MQW). The collective super-radiant mode shows enhanced emission rate for specific angles and frequencies. This behaviour correlates with the calculations demonstrating individual spots of the enhanced Purcell coefficient near the Bragg condition curve. This study provides a perspective for realization of surface emitting cavity-less lasers with distributed feedback.